Pemanfaatan Teknik Pengenalan Wajah Berbasis Opencv untuk Sistem Informasi Pencatatan Kehadiran Dosen - Moh. Farid Wajdi; Jagad Sugiantara (Fakultas Teknik Universitas Hamzanwadi, 2018)
Human face recognition (human face recognition) is a major branch in the field of biometric verification in addition to the introduction of eye retina, fingerprints and signature patterns and its application has been widely used in various network security system applications, door control systems, to the benefit of attendance recording system. The current study aims to utilize facial recognition techniques as data input for information systems that record the presence of lecturers at the Hamzanwadi University Faculty of Engineering. The technology base for developing the system support software is OpenCV and the Java programming language. This research was conducted with the design-science for IS research method that emphasizes the build and evaluate cycles. The build phase will be carried out using object-oriented rules while the evaluate stage is carried out by adopting the Technology Acceptance Model (TAM) framework.DOI : 10.29408/jit.v1i2.903